An Empirical Study of the Presidential Elections Effect on Stock Market in Taiwan, South Korea, Singapore, Philippine, and Indonesia - Liu, Ling-Fang (2007)
The behaviour of stock market around election periods has been investigated for several decades but the presidential elections held in Asian countries have not been analyzed in the previous studies. The main objective of this study is to examine the return pattern around presidential election period in the stock markets of Taiwan, South Korea, Singapore, the Philippines, and Indonesia during the sample period 1996-2005. It has been found that stock markets generate positive abnormal returns fifteen-day period before and after the presidential elections, and that the magnitude of abnormal return is greatest in the presidential elections held in less-free countries when an incumbent loses. In addition, other financial and political factors have been found to play an important role in influencing the return pattern around presidential elections. This dissertation may be of interest to investors and financial analysts, especially those who intend to put money into Asian stock market during the coming South Korea 2007 and Taiwan 2008 presidential elections.